Tuberculosis- Associated diseases: A comprehensive review - YATINDRA KUMAR,; MOHD. MUJAHID,; SHEO PRATAP SINGH, (International Journal of Pharma and Bio Sciences, 2018)
Sometimes patients with Tuberculosis (TB) infection may develop multiple complications, other diseases and comorbidities. The objective of this study was to represent TB associated with other diseases. A comprehensive review of the literature was performed to assess the association between TB and other diseases. Furthermore, the possible mechanisms by which other diseases can cause tuberculosis, the impact of tuberculosis on these diseases and their aftereffects related to the co-management of tuberculosis and these diseases were also studied.